ANALISIS PENDAPATAN AGROINDUSTRI GULA KELAPA DI KECAMATAN TEMPULING KABUPATEN INDRAGIRI HILIR - Dhany Wibowo; Evy Maharani; Eliza Eliza (Universitas Sebelas Maret, 2020)
Indragiri Hilir districtis is one of the main coconut-producer districts with a total production of up to 359,397 tons in Riau Province. This study aims to analyze the profit of coconut sugar agro-industry producer. The study was conducted in Karya Tunas Jaya village, Tempuling sub-district, Indragiri Hilir district. This location was chosen due to this village has a lot of hybrid coconut plantations and which are still active in processing downstream coconut sugar industry. This research was conducted for 6 months. To answer the research objectives used income analysis and return to cost ratio. The results showed that to produce a coconut sugar had to go through a long process, starting from collecting raw materials to molding and cooling coconut sugar. The average total processing cost of coconut sugar producer was Rp. 3,960,040.86/month and coconut sugar agro-industry producer profit was Rp. 4,845,866.67. Furthermore, the R/C ratio index of palm sugar agro-industry producer was 1.23 with an average profit of Rp. 885,825.80.